The LPS-induced neutrophil recruitment into rat air pouches is mediated by TNFα: likely macrophage origin - C-D. Arreto; C. Dumarey; M-A. Nahori; B. B. Vargaftig (Mediators of Inflammation)
The role of resident cells during the lipopolysaccharide (LPS)-induced neutrophil recruitment into rat air pouches was investigated. In this model, LPS (Escherichia coli, O55: B5 strain; 2–2000 ng) induced a dose– and time-dependent neutrophil recruitment accompanied by the generation of a tumour necrosis factor-α (TNFα)-like activity. Dexamethasone (0.05–5 mug) and cycloheximide (6 ng), injected 2 h before LPS into the pouches, inhibited the neutrophil recruitment and the generation of the TNFα-like activity, while the H1-receptor antagonist mepyramine (1 and 4 mg/kg, i.p., 0.5 h before LPS) and the PAF-receptor antagonist WEB 2170 (0.05 and 1 mg/kg, i.p., 0.5 h before LPS) had no effect. Purified alveolar macrophages (AM) were used to replenish the pouches of cycloheximide-treated recipient rats. AM provided by PBS-treated animals led to the recovery of the LPS-induced neutrophil recruitment and of the TNFα-like formation contrasting with those from cycloheximide-treated animals (1 mg/kg, i.p.). When delivered in situ, liposome-encapsulated clodronate, a macrophage depletor, significantly impaired both the LPSinduced neutrophil recruitment and the TNFα-like activity. An anti-murine TNFα polyclonal antibody (0.5 h before LPS) was also effective. These results emphasize the pivotal role of macrophages for LPS-induced neutrophil recruitment via the formation of TNFα.